The effect of 6-week EEG-biofeedback training in normobaric hypoxia and normoxia conditions on reaction time in elite judo athletes - Magdalena PROŃCZUK; Joanna MOTOWIDŁO; Ewelina LULIŃSKA; Dariusz T. SKALSKI; Jarosław MARKOWSKI; Jan PILCH; Maciej KOSTRZEWA; Artur TERBALYAN; Karol SKOTNICZNY; Adam MASZCZYK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: The purpose of this study was to evaluate the effect of Biofeedback Training in normoxic and normobaric hypoxic conditions on reaction times in judo athletes. Material and methods: The participants in the experimental group underwent thetha/beta1 training under simulated hypoxic conditions in a laboratory equipped with a normobaric hypoxia generation system (LOS-HYP1/3NU, Lowoxygen Systems, Germany), at a simulated altitude of 2500m above sea level (FiO2 = 15.5%). Each cycle of the study consisted of 15 training sessions. The training sessions lasted for 20 minutes, with 4 sets of 4 minutes each and a 1-minute break in between. In the initial phase, participants underwent EEG biofeedback training every other day. The control group followed the same frequency and duration of EEG biofeedback training sessions as the experimental group and demonstrated an identical pattern, but under normoxia conditions. Results: The results indicated significant differences in Theta/Beta ratio values after the 5th, 11th, and 15th training sessions between the hypoxia and normoxia groups. Moreover, theta/beta1 protocol in normobaric hypoxic conditions statistically significantly improved their complex reaction times after each training cycle compared to the control group in normoxia conditions. Conclusions: The findings indicate that neurofeedback training in normobaric hypoxia conditions may considerably enhance reaction skills, particularly complex reactions, in a sports context.